Affect of non-monetary benefit on employee performance - Abdullah, Nadia Azlin (2019)
The research objective is to examine whether non-monetary which include the recognition, job enrichment and promotion opportunities have a positive relationship on employee performance. The target respondent is staffed who are working at Melaka International College of Science and Technology (MiCoST). The quantitative research approach was adopted using five points Likert scale questionnaire and the data collection managed to achieve a percentage of 100 per cent which is 103 questionnaires returned which were derived from a total of 103 questionnaires. The collected data are being analysed using Statistical Package for Social Science (SPSS) software. This research engaged convenience sampling technique. Descriptive analysis, reliability analysis, Pearson correlation analysis and multiple regression will be used to analyse the collected data. The result shows that promotion opportunities have a positive and significant relationship with employee performance. Future researchers are recommended to an approached different type of respondent and test on different independent variables.